Corpo, consumo e biopolítica: diferentes idênticas convocações midiáticas para um estilo de vida feminino e ideal - Hermann, Renata Presa (2016)
In the group of interdisciplinary studies that characterize the field of Communication, this research analyzed the enunciation present on the covers of women s magazines CLAUDIA and TPM, starting from the following question: how are the communication and consumption strategies mobilized in the biopolitical calling discourse of the aforementioned magazines? We assume the following premises to develop an observation on the production dynamics of the biopolitical calling discourse and their relations with consumption practices: 1) the devices of control that were, originally, present in State institutions, are in contemporaneity inserted also in media discourses; and 2) the productions of sense created by media discourse of biopolitical calling in the analyzed magazines, reflect discourses of truth that are inserted in a logic proper to a discursive formation with specific conditions for production. The notion of biopolitics permeates our observation, dialoguing with paradigms of communication and consumption to map the biopolitical callings of the corpora, to identify the lifestyle that is promoted in the context of consumption, and to problematize the social production of senses created through the discourses of biopolitical calling in the articulation between communication and consumption. This is a transdisciplinary research that works with theoretical paradigms of communication, consumption, philosophy, discourse analysis and studies of the body. Authors like Prado, Hoff, Sibilia, Bruno and Silverstone serve as grounds for our observation on media callings; Canclini, Douglas&Isherwood and Rocha aid us in notions about consumption; Brandão and Orlandi guide us in the concepts of understanding about discourse in the ADF, from Pêcheux, and theory of discourse, from Foucault; finally, Foucault also serves as base for our research with his studies on production of power and knowledge about the bodies of individuals and populations, applying the concept of biopolitics. With the mapping of verbal and non-verbal texts, the identification of biopolitical callings that are present in the corpora and the categorization of these (imperative of happiness; need for continual improvement; a beautiful and healthy body; questioning of the status quo), we use the following analysis keys to problematize the social production of senses promoted by the analyses magazines: said and unsaid, conditions of production and positivity. We identify that CLAUDIA and TPM mobilize strategies of communication and consumption to produce discourses of biopolitical calling, yet the formats and strategies used are different in each one, as are the contracts of communication and the way of questioning their readers. The callings of CLAUDIA emphasize self-caring on an individual context, the contract of communication paints a woman that requires guidance, and the textual strategies use mainly the conative function of language. In turn, the callings by TPM go beyond selfcaring and question its readers for the management of life on a social context. Both ways of calling, besides their differences, press on the subject responsibility over their body, both in what refers to beauty care as well as health and productivity, which, in the dynamic of contemporary capitalism, is identified as a way, even if controlled, of power of the subject over their own body.